برصغیر ہند و پاک میں مسلم معاشرے کی تشکیل میں اسلامی احیا پسند تحریکوں اور شخصیات کا کردار: Role of Islamic Revivalist Movements and Individuals in Shaping the Direction of Muslims Scholarship in Indian Subcontinent - Lone, Niyaz Ahmad (FIKR-O NAZAR فکر ونظر, 2024)
The history of advent of Islam in India can be traced back in the trade relations between Arabs and India. Subsequently, after the arrival of Islam in Arab land, the Arab traders played a role of missionaries. Then gradually Islam was disseminated through peaceful means in the Indian subcontinent. In this regard, Sufis played an important character. After that, Islam became a dominant faith in Indian society, especially during Muslim rule Islam spread far and wide in the Subcontinent. However, later on, due to European Colonialism, Muslim rule showed decay in India. Consequently, the Islamic culture was prone to devastation. Similarly, at internal level ignorance of the Muslims was another reason of the decline of the Islamic culture. So, Islam underwent a dire need of reform and revival. Hence, afterward there were multiple movements which attempted to reform the Muslim society in order to awake the religious consciousness of the Muslims. Jihād movement, Deoband movement, Aligarh movement, Nadwat-ul- ‘Ulama, Jam ‘āt-i-Islami, etc., were some of the movements which contributed immensely towards the enhancement of intellectual and religious dimension of the Muslim society. These all movements attempted to reform the religious aspect of the Muslims according to the diverse and dynamic nature of the society. They emphasized on different aspects of Islamic teachings and attempted to permeate Islam in the changing circumstances of the society. Some focused on the political aspect of Islam, some on pure theological dimension of Islam, and some attempted to counter the modern challenges through a rational understanding of Islam. Hence, they accordingly deliberated on the revival of Islam. The common thing among these movements is that, almost all these movements trace the origin of their thought in the religious ideas of Shah Wali-Allah whose comprehensive thought left a deep impact on these subsequent movements.